A national pediatric otolaryngology fellowship virtual dissection course using 3D printed simulators. (November 2022) - Michaels, Ross E.; Zugris, Nicholas V.; Cin, Mitchell D.; Monovoukas, Demetri A.; Koka, Krishna K.; Smith, Connor; Bohm, Lauren; Kim, Jennifer; Green, Glenn; Roby, Brianne; Jabbour, Noel; Lind, Meredith; et al.
Abstract: Objective: Our objective was to create and evaluate a novel virtual platform dissection course to complement pediatric otolaryngology fellowship training in the setting of the COVID-19 pandemic. Methods: A four-station, four-simulator virtual course was delivered to pediatric otolaryngology fellows virtually using teleconferencing software. The four stations consisted of microtia ear carving, airway graft carving, cleft lip repair, and cleft palate repair. Fellows were asked to complete pre- and post-course surveys to evaluate their procedural confidence, expertise, and attitudes towards the course structure. Results: Statistical analysis of pre-course survey data showed fellows agreed that simulators should play an important part in surgical training (4.59 (0.62)); would like more options for training with simulators (4.31 (0.88)); and would like the option of saving their simulators for later reference (4.41 (0.85)). Fellows found the surgical simulators used in the course to be valuable as potential training tools (3.96 (0.96)), as competency or evaluation tools (3.91 (0.98)), and as rehearsal tools (4.06 (0.93)). Analysis showed a statistically significant improvement in overall surgical confidence in performing all four procedures. Conclusion: This virtual surgical dissection course demonstrates 3D printed surgical simulators can be utilized to teach fellows advanced surgical techniques in a low-risk, virtual environment. Virtual platforms are a viable, highly-rated option for surgical training in the setting of restricted in-person meetings and as a mechanism to increase access for fellows by reducing costs and travel requirements during unrestricted periods. Highlights: Can we as otolaryngologist diversify the surgical training opportunities through the use of teleconferencing and 3D printed surgical simulators? Pediatric otolaryngology fellows self-reported increased surgical confidence in all four procedures taught during a virtual dissection course using teleconferencing and 3D printed surgical simulators. Trainees agreed that the virtual format was an acceptable alternative to an in person course with no qualifiers; both when, in-person courses are restricted, and as an option when they are non-restricted. Virtual platform dissection courses are a highly-rated option for surgical training in the setting of restricted in-person meetings.